Intrastromal Corneal Ring Segment Implantation (Keraring 355°) in Patients with Central Keratoconus: 6-Month Follow-Up - Khosrow Jadidi; Seyed Aliasghar Mosavi; Farhad Nejat; Mostafa Naderi; Leila Janani; Sara Serahati (Journal of Ophthalmology)
We evaluate the efficacy and safety of Keraring 355° intrastromal corneal ring segment (ICRS) implantation aided by PocketMaker microkeratome for the correction of keratoconus. Patients underwent ICRS insertion using mechanical dissection with PocketMaker microkeratome and completed 6 months of follow-up. Uncorrected visual acuity (UCVA), best spectacle-corrected visual acuity (BSCVA), refraction, topographic findings, safety, efficacy index, and adverse events were reported for six months postoperatively. We evaluated 15 eyes of 15 patients (12 men) with a mean age of 28.87 ± 6.94 years (range 21–49 years). At final postoperative examination, there was a statistically significant reduction in the spherical equivalent refractive error compared to preoperative measurements (−5.46 ± 1.52 to −2.01 ± 1.63 D, P< 0.001). Mean preoperative UCVA (logMAR) before implantation was 0.79 ± 0.48, and postoperative UCVA was 0.28 ± 0.15, P= 0.001. Mean preoperative BSCVA (logMAR) before implantation was 0.36 ± 0.21; at final follow-up examination BSCVA was 0.18 ± 0.9, P= 0.009. Mean K decreased from 48.33 to 43.31 D, P< 0.001. All patients were satisfied with ICRS implantation; 86.7% were moderately to very happy with the results. No intraoperative or postoperative complications were demonstrated. This preliminary study shows that ICRS (Keraring 355°) implantation is an efficient, cost-effective, and minimally invasive procedure for improving visual acuity in nipple type keratoconic corneas.